Viscoelasticity of upper mantle utilizing high-resolution techniques - Cao, R (2020)
In this study, we developed a high-temperature, uniaxial creep apparatus to investigate the nonlinear viscoelasticity of geological materials at a wide range of temperatures (room temperature to 1330°C), frequencies (0.01 Hz to 100 Hz), and bias stresses (maximum load of 5 kN). This apparatus allows us to conduct creep tests (i.e., constant bias stress) and forced oscillation tests simultaneously, and these capabilities allow us to investigate viscoelastic phenomena relevant to postseismic relaxation, glacial isostatic adjustment, and tidal dissipation in exoplanets. We characterize the complex spring compliance of the apparatus by conducting several calibration experiments using single-crystal sapphire. Based on experiments conducted on sapphire samples with different lengths, we demonstrate that the apparatus compliance is dependent on frequency and sample length, but not on the oscillation amplitude or bias stress. We validate this calibration by measuring the viscoelastic properties of aluminum and stainless steel and comparing our results to previously published results at similar conditions. Based on this calibration, we constrain the parameter space within which reliable measurements of attenuation and Young’s modulus can be made with this apparatus. We use this newly calibrated apparatus to conduct a series of experiments to examine viscoelasticity in single-crystal San Carlos olivine. Our results reveal that an increase in the bias stress causes an increase in attenuation, demonstrating that attenuation increases with increasing dislocation density. The magnitude of attenuation ranges from 0.1 to 100, and the Young’s modulus ranges from 40 GPa to the unrelaxed modulus. These experiments demonstrate that the critical stress amplitude demarcating the transition from linear to nonlinear viscoelasticity is approximately at ~1 MPa. Furthermore, these experiments exhibit a peak in attenuation as a function of stress amplitude at approximately 1.2 MPa stress amplitude, although the position of the peak depends on the bias stress and temperature. The shape of hysteresis loops is inconsistent with models for attenuation based on dislocation breakaway from point defects. Instead, we suggest our data are consistent with nonlocalized friction models in which the restoring force is controlled by the backstress associated with the long-range stress fields of dislocations and the onset of nonlinear dissipation is controlled by the plastic yield strength of olivine.